2021
DOI: 10.1093/eurpub/ckaa244
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-term health impact of exposure to gas-mining induced earthquakes and related environmental stressors

Abstract: Background Little is known about the public health impact of chronic exposure to physical and social stressors in the human environment. Objective of this study was to investigate the immediate and long-term health effects of living in an environment with gas-mining induced earthquakes and related stressors in the Netherlands. Methods Data on psychological, somatic and social problems recorded routinely in electronic health r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…The primary objectives of these literature reviews are twofold: firstly, to compile a comprehensive overview of the pandemic's effects on the general population and vulnerable groups; secondly, to enhance monitoring efforts by identifying knowledge gaps and providing input for further, in-depth research, thereby informing other aspects of the monitoring process. The yearly repetition of the literature review enables the assessment of the impact of the pan- The outcome parameters used in the Integrated Health Monitor COVID-19 are based on earlier health disaster research [18][19][20][21][22][23][24], such as (posttraumatic) stress and suicidal thoughts. Other outcome parameters included are those that were already present in the existing research structures for comparison with the pre-pandemic situation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary objectives of these literature reviews are twofold: firstly, to compile a comprehensive overview of the pandemic's effects on the general population and vulnerable groups; secondly, to enhance monitoring efforts by identifying knowledge gaps and providing input for further, in-depth research, thereby informing other aspects of the monitoring process. The yearly repetition of the literature review enables the assessment of the impact of the pan- The outcome parameters used in the Integrated Health Monitor COVID-19 are based on earlier health disaster research [18][19][20][21][22][23][24], such as (posttraumatic) stress and suicidal thoughts. Other outcome parameters included are those that were already present in the existing research structures for comparison with the pre-pandemic situation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Box 2 provides examples of findings from both data sources in short-cycle monitoring. Based on quarterly panel surveys among youth and young adults (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) since September 2021, it was concluded that the mental health of this population deteriorated after the last severe lockdown period in the Netherlands during the winter of 2021/2022. The first measurement of 2022, for instance, indicated an increase in suicide ideation experienced by participants during the last three months from 8.5% (December 2021) to 16.8% (March 2022).…”
Section: Short-cycle Monitoringmentioning
confidence: 99%
“…Zo is gezondheidsonderzoek gestart na de vuurwerkramp in Enschede (2000), de Nieuwjaarsbrand in Volendam (2001), de poldercrash (2009) en de ramp met vlucht MH17 (2014). Het enige voorbeeld van longitudinaal GOR bij een langslepende crisis in Nederland betreft de aardbevingsproblematiek in Groningen [ 10 ].…”
Section: Gezondheidsonderzoek Bij Rampenunclassified